Nursing care for ischemicstroke and Tetralogy of Fallot (ToF) in the regional general hospital of Banda Aceh: Case study - Dwi Afraah Syaakirah; Sufriani Sufriani (Indonesian Journal of Health Science, 2026)
Ischemic stroke is an acute neurological disorder caused by impaired blood flow to brain tissue, resulting in disruption of oxygen and nutrient supply and leading to cerebral tissue damage. In children, this condition may be associated with congenital heart defects such as Tetralogy of Fallot, which causes chronic hypoxemia and increased blood viscosity, thereby elevating the risk of cerebral thrombosis. This case study aimed to analyze nursing care for a pediatric patient An. A diagnosed with ischemic stroke accompanied by Tetralogy of Fallot in the Arafah 1 inpatient ward of dr. Zainoel Abidin Regional General Hospital in Banda Aceh. The identified nursing problems included decreased intracranial adaptive capacity, ineffective breathing pattern, ineffective airway clearance, nutritional deficit, ineffective peripheral perfusion, impaired physical mobility, and risk of aspiration. The nursing interventions implemented included intracranial pressure management, respiratory management, nutritional management, peripheral perfusion management, energy management, mobility management, and aspiration prevention. Evaluation of care outcomes for An. A showed that ineffective breathing pattern, ineffective airway clearance, and ineffective peripheral perfusion were resolved; decreased intracranial adaptive capacity, fatigue, and risk of aspiration were partially resolved, while nutritional deficit and impaired physical mobility remained unresolved. Therefore, continuous care and comprehensive evaluation are required during hospitalization. The findings of this scientific paper are expected to contribute for optimizing nursing care for pediatric patients with ischemic stroke accompanied by Tetralogy of Fallot, as well as supporting the improvement of professional, comprehensive, and continuous nursing services.